Sturmian expansions for two-electron atomic systems: Singly and doubly excited states - Frapiccini, Ana Laura (2010)
We present a configuration interaction (CI) method based on the Sturmian expansion for bound states of a two-electron atomic system. These Sturmian functions are solutions of one-electron quantum mechanical problems, where the eigenvalue is the magnitude of a short-range potential. Also, they fulfill the long-range boundary conditions of Coulomb potentials. We choose to expand the Sturmians of the CI basis using L2 Laguerre-type functions. We compute ground and single-excited states energies for He and H. Moreover, we are able to obtain energies and widths of double excited states of He, using a Sturmian basis with outgoing boundary conditions. In all cases, our ansatz outperforms other CI calculations, for similar basis size. © 2010 The American Physical Society.